The Estimation of Rainwater Acidity Level based on the Ambient Air Pollutants Concentration (Case Study: DKI Jakarta) - Ana Turyanti; C Chaerunnisa (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2017)
Nowadays, acid rain is a common phenomenon occurring in metropolitan city, such as Jakarta. Human activities including transportation and industries in and surrounding this city have increased pollutants in the atmosphere, which lead to an increased of acid rain events. Analyzing on rainwater pH is common approach to assess whether an acid rain occurs or not. However, information on this pH value for greater Jakarta is limited. Here we used a combined of Henry's law approach and Weather Research Forecasting-Chemistry (WRF-Chem) to estimate rainwater pH in Jakarta. The WRF-Chem was employed to generate SO2 and NO2 concentrations. Results showed that rainwater pH is below the threshold (pH = 5.6) in observation and modeling (Henry’s approach) throughout greater Jakarta. Rainwater pH showed a diurnal fluctuation with low value during night and morning, but high value at afternoon. Likely, season contributed to distribution of acid rain. Based on Henry’s approach, some regions (Bundaran HI, Kebon Jeruk, and Jagakarsa) revealed a high potency of acid rain for rainy season as indicated by the H+ concentration. On other hand, a high potency of acid rain during dry season was observed in Kelapa Gading and Bundaran HI. Our findings indicated that traffic may influence on rain acid events as shown by a high H+ concentration in Bundaran HI both dry and wet seasons.